Pengertian Media, Tujuan, Fungsi, Manfaat dan Urgensi Media Pembelajaran - Aisyah Fadilah; Kiki Rizki Nurzakiyah; Nasywa Atha Kanya; Sulis Putri Hidayat; Usep Setiawan (Pusat Riset dan Inovasi Nasional, 2023)
In this day and age, the use of media is very helpful for educators in a certain learning or training, namely as a tool to facilitate the implementation of teaching and learning, which is expected to run effectively to achieve predetermined learning goals. Meanwhile, the purpose of its use is to make it easier for educators to convey information on learning materials that will be conveyed so that they are easy to understand and understand making it interesting to use media for students to be happier in the learning process. So media is an instrument or tool to deliver learning material so that students are able to understand what is conveyed using media tools such as markers, package books or reading, whiteboards, including teachers and the environment is also a medium for implementing information delivery. In learning media, there are media used by teachers, namely visual (media with delivery using something that can be seen by the sense of sight), audio-visual (media with elements of conveying information using sound also contains an element of image, such as video), audio (information delivery using voice messages or closely related to the sense of hearing). Along with the advancement of media technology, it has a variety of tools that make it easier for teachers to learn using current technology media such as: cellphones, computers, laptops, and other applications that are used to obtain other sources of information.